The portrayal of refugees in Canadian newspapers: The impact of the arrival of Tamil refugees by sea in 2010 - Stelian Medianu; Alina Sutter; Victoria Esses (IdeAs)
News media make an essential contribution to the way in which the public processes and understands controversial issues such as the arrival of refugees in western countries. Indeed, they can have an important role in shaping the public’s responses to these issues by framing arguments to encourage a particular interpretation of an issue. The current research investigates how refugees were portrayed before and after the controversial arrival of a ship carrying Tamil refugees to Canada in August 2010. The study was based on the content analysis of 102 articles published in six Canadian newspapers six months before and six months after the event. The newspapers were selected based on their large circulation and diverse political slants. The analyses revealed substantial variation in the extent to which the newspapers reported on the issue of refugee arrivals, as well as in their portrayals of refugees. Liberal newspapers were more likely than conservative newspapers to include reports on issues surrounding refugees and were more likely to portray refugees as victims. Also, the analyses demonstrated the impact of the arrival of the Tamil refugee ship on the portrayal of refugees. Whereas before the event refugees were portrayed more in terms of false claims for refugee status, after the event refugees were portrayed more in terms of being either criminals and terrorists or victims. These results have important implications for how refugees are perceived and treated in society, including what kind of policies are implemented to handle refugee claims and what type of assistance is provided to refugees.